Evaluation of the Bactericidal Activity of a Hyaluronic Acid-Vehicled Clarithromycin Antibiotic Mixture by Confocal Laser Scanning Microscopy - Narcisa Mandras (Applied Sciences, 2020)
Confocal laser scanning microscopy (CLSM) was used to evaluate the antibacterial effect and depth of action of a novel clarithromycin-containing triple antibiotic mixture, which was proposed for root canal disinfection in dental pulp regeneration. A previous study reported that this mixture had no tooth discoloration effects in vitro. After infection with Enterococcus faecalis for 3 weeks, the dentinal tubules in the cylindrical root specimens were exposed to different antibiotic mixtures: ciprofloxacin, metronidazole and minocycline (3-MIX); ciprofloxacin, metronidazole and clarithromycin (3-MIXC) and ciprofloxacin and metronidazole (2-MIX). Each antibiotic formulation was mixed with macrogol (MG) or hyaluronic acid (HA) vehicles. CLSM and viability staining were used to quantitatively analyze the mean depth of the antibacterial effect and the proportions of dead and live bacteria inside the dentinal tubules. The 3-MIX and 3-MIXC demonstrated a similar depth of action. The mean proportion of dead bacteria was similar in the 3-MIX and 3-MIXC groups, and both were statistically higher than that of 2-MIX (p = 0.014). Each antibiotic mixture showed a higher bactericidal efficacy if conveyed with HA, compared to MG (3-MIX, p = 0.019; 3-MIXC, p = 0.013 and 2-MIX, p = 0.0125). The depth of action and the antibacterial efficacy of 3-MIXC seemed comparable with 3-MIX.